Respuesta :
Answer:
1) (fg)(x) = 4x^2 + 6x + 2
2) (f-g)(x) = -3x -1
3) (f+g)(3) = 18
Step-by-step explanation:
Given:
f(x) = x+1
g(x) = 4x + 2
1) To find (fg)(x)
(fg)(x) = f(x) * g(x)
= (x+1)(4x+2)
= (4x^2 +2x+4x+2)
(fg)(x) = 4x^2 + 6x + 2
2) To find (f-g)(x)
(f-g)(x) = f(x) - g(x)
= (x+1) - (4x+2)
(f-g)(x) = -3x -1
3) To find (f+g)(3)
(f+g)(x) = f(x) + g(x)
(f+g)(3) = f(3) + g(3)
= (3+1) + (4(3)+2)
(f+g)(3) = 18
Answer:
a) 4x^2 +6x + 2
b) -3x - 1
c) 18
Step-by-step explanation:
f(x) = x + 1
g(x) = 4x + 2
a) (f*g)(x)
= f(x) * g(x)
= (x + 1) (4x + 2)
= 4x^2 + 2x +4x + 2
= 4x^2 + 6x + 2
b) (f-g) (x)
= f(x) - g(x)
= (x + 1) - (4x + 2)
= x + 1 - 4x - 2
= x - 4x + 1 - 2
= -3x - 1
c) (f+g)(3)
= (f+g)(x) = f(x) + g(x)
= (x + 1) + (4x + 2)
= x + 1 + 4x + 2
= x + 4x + 1 + 2
= 5x + 3
put x =3
= 5(3) + 3
= 15 + 3
= 18